Learning by Doing : The Japanese PHRD Fund and Capacity Development - Potten, David (2012)
The Government of Japan has been supporting capacity development through the World Bank for 17 years. It has provided grants under its Policy and Human Resources Development (PHRD) Fund to support graduate scholarships, training activities, and preparation and implementation of loans and credits. Various evaluations have shown all three types of assistance to be effective, and grants to support project preparation in particular have generally been judged highly successful, because they have contributed to rapid and high-quality preparation of lending operations. A recent independent evaluation has shown that these grants have also contributed substantially to human capacity development in recipient countries, because recipient execution has led to strong ownership, the nature of project preparation has put a premium on capacity development needs, and the design of the program has favored capacity development activities.